A REVIEW ON ANTIOXIDANT METHODS - Sunitha Dontha (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT To provide an outlook of the various available methods of antioxidant activity. Various available in vitro and in vivo methods are listed and the procedure to perform the method, its mechanism is also explained in brief. 1,1-diphenyl-2-picrylhydrazyl method was found to be used mostly for the in vitro antioxidant activity evaluation purpose while lipid peroxidation was found as mostly used in vivo antioxidant assay. An ethanol was with the highest frequency as a solvent for extraction purpose. Summarized information on the various methods available provides with reliable information to confirm the benefits of antioxidant effects. Keywords: Antioxidant activity, Reactive oxygen species, Free radical, 1,1-diphenyl-2-picrylhydrazyl, Flavonoid.